PENGARUH KEPERCAYAAN TAHUN ALIF TERHADAP KEHARMONISAN KELUARGA DALAM PERSPEKTIF HUKUM ISLAM (STUDI KASUS KECAMATAN JONGGOL KABUPATEN BOGOR TIMUR) - Alif Fajar As-Shiddiqy; M Kholil Nawawi; Kamalludin (KOLONI, 2022)
Belief in the Year of Alif is a myth that spreads in the community of Jonggol District, East Bogor Regency, where people believe that if you do big events such as weddings, circumcision, thanksgiving and others in that year it will bring disaster. This study is to determine the effect of the belief in the Year of Alif on family harmony in the perspective of the people of the District of Jonggol and to determine the perspective of Islamic law regarding the belief of the Year of Alif on family harmony. The type or method used is descriptive qualitative, with data collection techniques used are interview and documentation methods. The results of the study conclude that the influence of belief in the Year of Alif on family harmony does not affect family harmony but belief in the Year of Alif causes shirk so that it cannot be an excuse for not doing big events, especially holding weddings in the year of Alif. Based on the conclusion above, people should not believe in the myth of the Year of Alif which is contrary to the teachings of Islam. And prevent the occurrence of acts of shirk by believing in the year of Alif subtly without violence so that people do not carry out traditional practices that are not sourced from Islamic law. Keywords: Alif Year, Family Harmony, Islamic Law